„Czy wszyscy Żydzi mają rogi?”. Obraz „obcego” na stadionach piłkarskich na przykładzie Krakowa .......... 59 - Stypuła, Łukasz (Niematerialne dziedzictwo kulturowe w teorii i praktyce, 2021)
THE IMAGE OF THE STRANGER IN FOOTBALL STADIUMS ON THE EXAMPLE OF KRAKÓWWhere does the strangeness begin? As it may seem, the answer to this question is connected with the scale and measure of “normality” which we accept. Do we place it in our reality, or it will be rather rooted in the world of others, strangers? In the first case, behaviour of others appears as an anomaly, deviation from the normal, accepted by my group as customary. In the second case, my behaviour may appear as an anomaly. In Kraków, quite a peculiar transformation took place – concerning the structure of “the image of the Jew” and “the image of the stranger”, which led to unique incongruousness of these images. Is reality of one’s own world threatened by derealisation in the case of “the pressure of strangeness”? Or maybe quite the contrary, as Zbigniew Benedyktowicz writes in his “Primer of the Identity” that due to the meeting with others, strangers, we can recognise ourselves, our own identity? What is the role of the stereotype and image in the reflection on symbolic culture? What gives us larger cognitive freedom in the attempt of finding the stranger in culture? Search for such a person means also observing and recognising of signs in a city sphere, phenomena, which trigger some kind of communication, and I will try trace just this intricacy on the example of the Kraków world of football fans.